Antioxidant and Pro-Oxidant Capacities as Mechanisms of Photoprotection of Olive Polyphenols on UVA-Damaged Human Keratinocytes - Raffaella Marina Lecci; Isabella D’Antuono; Angela Cardinali; Antonella Garbetta; Vito Linsalata; Antonio F. Logrieco; Antonella Leone (Molecules, 2021)
A wide variety of polyphenols are reported to have considerable antioxidant and skin photoprotective effects, although the mechanisms of action are not fully known. Environmentally friendly and inexpensive sources of natural bioactive compounds, such as olive mill wastewater (OMWW), the by-product of olive-oil processing, can be considered an economic source of bioactive polyphenols, with a range of biological activities, useful as chemotherapeutic or cosmeceutical agents. Green strategies, such as the process based on membrane technologies, allow to recover active polyphenols from this complex matrix. This study aims to evaluate the antioxidant, pro-oxidant, and photoprotective effects, including the underlying action mechanism(s), of the ultra-filtered (UF) OMWW fractions, in order to substantiate their use as natural cosmeceutical ingredient. Six chemically characterized UF-OMWW fractions, from Italian and Greek olive cultivar processing, were investigated for their antioxidant activities, measured by Trolox Equivalent Antioxidant Capacity (TEAC), LDL oxidation inhibition, and ROS-quenching ability in UVA-irradiated HEKa (Human Epidermal Keratinocytes adult) cultures. The photoprotective properties of UF-OMWW were assayed as a pro-oxidant-mediated pro-apoptotic effect on the UVA-damaged HEKa cells, which can be potentially involved in the carcinogenesis process. All the UF-OMWW fractions exerted an effective antioxidant activity in vitro and in cells when administered together with UV-radiation on HEKa. A pro-oxidative and pro-apoptotic effect on the UVA-damaged HEKa cells were observed, suggesting some protective actions of polyphenol fraction on keratinocyte cell cultures.